A NEW RHYNCHOLITE SUBGENUS NERODENKOINA FROM THE APTIAN OF THE MOUNTAINOUS CRIMEA - Komarov V.N. (My University, 2003)
A new rhyncholite Hadrocheilus (Nerodenkoina) aenigmatosus subgen. et sp. nov. is described from the Aptian of the Mountainous Crimea.
Keywords: Aptian; Mesozoic::Cretaceous::Lower::Aptian; Мезозой::Меловая::Нижний::Аптский